[NN] bidentate coordination metal catalyst based on quinoline skeleton as well as preparation method and application of [NN] bidentate coordination metal catalyst
Through the condensation of quinoline-8-formaldehyde and aniline and the reaction of MMe4, a quinoline framework [NN] bitotonic coordination metal catalyst was prepared, which solved the problem of difficult to provide high-temperature quinoline framework [NN] bitotonic metal catalyst in the prior art, and achieved efficient polyolefin elastomer synthesis.
Patent Information
- Application Number
- CN202510031571.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The prior art is difficult to provide a high temperature quinoline skeleton [NN] bitotonic metal catalyst suitable for industrial production for the synthesis of polyolefin elastomers.
The quinoline skeleton [NN] bitodental coordination metal catalyst was prepared by p-TsOH between quinoline-8-formaldehyde and aniline.
It has achieved high catalytic activity, good copolymerization performance and excellent high temperature resistance, and is suitable for the preparation of polyolefin materials with high temperature solution polymerization.
Smart Images

Figure CN119823172A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a coordination polymerization metal catalyst, in particular to a [NN] bidentate coordination metal catalyst based on a quinoline skeleton, a preparation method thereof and application in the field of polyolefins. Background Art
[0002] Polyolefin elastomers (POEs) are a new type of material with properties between traditional thermoplastics and elastomers (such as rubber). They are copolymerized with ethylene and other α-olefins such as 1-octene, 1-butene or 1-hexene. Polyolefin elastomers (POEs) are widely used in automobiles, photovoltaic packaging, clothing and other fields due to their flexibility, elasticity, low density and easy processing.
[0003] The production of polyolefin elastomers adopts the high-temperature solution method because the process can improve the catalyst activity and reaction rate at higher temperatures, and evenly distribute the monomers through the solvent, so as to accurately control the molecular weight distribution and comonomer content of the polymer, and produce low crystallinity and high elasticity materials. In addition, the solution method is suitable for processing high α-olefin content systems, has higher product uniformity and processing flexibility, and the solvent is easy to recycle, which is environmentally friendly and economical, and is an ideal choice for industrial production of POEs.
[0004] Constrained geometry catalyst (CGC) was successfully used in the commercial production of POEs in the 1990s due to its good high temperature resistance (Chem. Rev. 1998, 98, 2587-2598). However, the synthesis difficulty of CGC catalyst is relatively high and the technical route is complicated; non-metallocene catalysts have been rapidly developed due to their strong structural adjustability and simple synthesis process. In 1999, Fujita et al. reported [NO] bidentate coordinated salicylaldehyde imine titanium and zirconium metal catalysts (FI catalysts) (Chem. Rev. 2011, 111, 30, 2363-2449), but their high temperature resistance is poor. In 2000, Union Carbide reported [NN] bidentate coordinated pyridine-amine zirconium and hafnium metal catalysts, which are suitable for high temperature solution polymerization (Acc. Chem. Res. 2015, 48, 2004-2016). Kloin reported [NN] bidentate coordinated amino-quinoline zirconium and hafnium metal catalysts (Organometallics 2012, 31, 6244-6251). Although the catalyst provided good high temperature resistance and copolymerization performance, it used expensive Pd catalyst to catalyze the coupling reaction during the ligand synthesis process, which made it difficult to apply industrially.
[0005] Therefore, providing a catalyst suitable for industrial synthesis of polyolefin elastomers has become a technical problem that the art has been eager to solve. Summary of the invention
[0006] The present invention aims at solving the problems existing in the prior art and provides a quinoline skeleton [NN] bidentate metal catalyst which is resistant to high temperature and suitable for industrial application.
[0007] Another object of the present invention is to provide a method for preparing a quinoline skeleton [NN] bidentate metal catalyst with low cost and high yield.
[0008] Another object of the present invention is to provide an application of a quinoline skeleton [NN] bidentate metal catalyst in the preparation of polyolefins.
[0009] The present invention provides a quinoline skeleton [NN] bidentate coordination metal catalyst, the structural formula of which is shown in formula (I):
[0010]
[0011] Wherein, M is selected from any one of titanium, zirconium or hafnium, and R1, R2, and R3 are selected from any one of fluorine, chlorine, bromine, iodine, and alkyl.
[0012] Preferably, the quinoline ligand structural formula of the quinoline skeleton [NN] bidentate coordination metal catalyst is selected from any one of the formula (II):
[0013]
[0014] The present invention provides a method for preparing the above-mentioned quinoline skeleton [NN] bidentate metal catalyst, comprising the following steps:
[0015] Under nitrogen atmosphere, 0.6-1.5 g of quinoline-8-carboxaldehyde is dissolved in 10-30 mL of ethanol solvent, the molar concentration of the ethanol solvent is 0.2-1.0 mol / L, 1.0-1.5 molar equivalents of aniline and 5-10 mg of p-toluenesulfonic acid are added, and the mixture is reacted at room temperature for 3 hours; after removing the ethanol under reduced pressure, anhydrous methanol is added for extraction and filtration to obtain a quinoline-imine ligand; 1.0-1.2 molar equivalents of metal chloride MCl4 are dissolved in 10-50 mL of anhydrous solvent, 4.0-6.0 molar equivalents of methylmagnesium bromide are added, and the mixture is stirred at -20--50° C. for 2 hours under nitrogen protection, and then 1 molar equivalent of quinoline-imine ligand is added, and the mixture is stirred at -20--50° C. for 2 hours and at room temperature for 4 hours; the solvent is removed under reduced pressure, extracted with a good solvent, and the filtrate is concentrated to obtain a quinoline skeleton [NN] bidentate coordination metal catalyst.
[0016] The anhydrous solvent is selected from any one of benzene, toluene and xylene; the good solvent is selected from any one of n-hexane, cyclohexane, n-pentane, n-heptane and toluene.
[0017] The metal chloride MCl4 is selected from one of TiCl4, ZrCl4 and HfCl4.
[0018] The present invention also provides the use of the above-mentioned quinoline skeleton [NN] bidentate coordination metal catalyst in the preparation of polyolefins.
[0019] In the above application, the olefin monomer in the polyolefin is one or more of ethylene, propylene, 1-butene, 1-hexene, 1-octene, styrene, and norbornene.
[0020] In the above application, the quinoline skeleton [NN] bidentate coordination metal catalyst is used in combination with a co-catalyst to catalyze olefin polymerization, and the co-catalyst is one or more of trispentafluorophenyl boron, trityltetrakis(pentafluorophenyl)borate, alkylaluminum, and aluminoxane.
[0021] Preferably, the alkylaluminum is trimethylaluminum, triethylaluminum, triisobutylaluminum or tri-n-hexylaluminum; and the aluminoxane is methylaluminoxane, ethylaluminoxane or isobutylaluminoxane.
[0022] In the olefin polymerization reaction, the polymerization temperature is 0-200° C., the polymerization pressure is 0.1-5 MPa, and the polymerization solvent is one or more of toluene, xylene, n-hexane, and cyclohexane.
[0023] The advantages and effects of the present invention are as follows:
[0024] In the present invention, a series of new quinoline-amine ligands are directly synthesized by p-TsOH-catalyzed aldehyde-amine condensation between quinoline-8-carboxaldehyde and various anilines. The quinoline-amine metal catalyst is obtained by a one-pot reaction of the obtained ligand and MMe4 (M = Ti, Zr or Hf) obtained by in situ synthesis. The synthesis is simple, the raw materials are readily available, the product yield is high, and the catalytic activity is high (1.62×10 7 g(POE)·mol -1 (Hf) h -1 ), good copolymerization performance (alpha olefin insertion rate is greater than 21.6 mol%); it also exhibits excellent high temperature resistance (greater than 140°C) and is suitable for high temperature solution polymerization to prepare polyolefin materials.
[0025] The obtained quinoline skeleton [NN] bidentate coordination metal catalyst was used in the synthesis of polyolefin elastomers. It was found that by changing the substituents on the catalyst structure, the molecular weight of the obtained polymer and the insertion rate of alpha olefins can be effectively improved; it can promote the development of my country's high-end polyolefin chemical industry and provide a new direction for the development of the polyolefin materials field. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the H NMR spectrum of catalyst C1.
[0027] Figure 2 This is the H NMR spectrum of catalyst C2.
[0028] Figure 3 This is the H NMR spectrum of catalyst C3.
[0029] Figure 4 This is the H NMR spectrum of catalyst C4.
[0030] Figure 5 This is the H NMR spectrum of catalyst C5.
[0031] Figure 6 This is the H NMR spectrum of catalyst C6. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further explained below in conjunction with specific implementation methods. However, it should be noted that the specific implementation methods are only a specific implementation and explanation of the essence of the technical solution of the present invention, and should not be understood as a limitation on the protection scope of the present invention.
[0033] Definition and explanation of terms: The raw materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources or prepared by known methods; the experimental methods used in the following examples, unless otherwise specified, are conventional methods known in the art; the concentrations in the following examples, unless otherwise specified, are molar concentrations.
[0034] The compounds synthesized in the following examples were characterized by infrared spectrometer and nuclear magnetic resonance spectroscopy.
[0035] The molecular weight and molecular weight distribution of the polymer obtained in the following polymerization examples were obtained by high temperature gel chromatography GPC-IR at 150°C, using 1,2,4-trichlorobenzene as solvent. The melting points of the polymers were determined by conventional DSC (Q2000) methods, and the polymerization activities of the polymers were calculated according to the following formula: polymerization activity = polymer mass / (catalyst molar amount × polymerization time). The calculation method of 1-octene insertion rate is referenced to (Macromolecules 1999, 32, 3817, Macromolecules 2007, 40, 6879). The high temperature nuclear magnetic resonance of the polymer was obtained by using Bruker AC400 at 125°C with deuterated o-dichlorobenzene as solvent.
[0036] The methylaluminoxane (MAO) used in the examples was purchased from an external source. In the following examples, Al / Hf is defined as the molar ratio of the metal Al in the cocatalyst MAO to the Hf in the metal complex, rather than the molar ratio of the aluminum element to the metal Hf.
[0037] The synthesis of the complexes in the following examples is carried out according to the following reaction equation:
[0038]
[0039] Wherein, M = Ti, Zr, Hf.
[0040] Synthesis Example 1, Preparation of Catalyst Cat 1
[0041] Weigh 0.79g of quinoline-8-carboxaldehyde (5mmol), add 20mL of anhydrous ethanol, slowly add 0.61g of 2,6-dimethylaniline (5mmol) at room temperature, add 5mg of p-toluenesulfonic acid to catalyze the reaction for 3 hours, use a rotary evaporator to remove ethanol under reduced pressure, where the rotary evaporation temperature is 60°C, the vacuum degree is 0.7bar, and the speed is 120 rpm. Add 5mL of anhydrous methanol and stir for 5 minutes, filter, and obtain 8-(2,6-Me2-C6H3-N=CH)-quinoline ligand L1 1.12g, with a yield of 85%. NMR data 1 H NMR(400MHz,Chloroform-d)δ8.90(dd,J=3.9,1.7Hz,1H),8.83(s,1H),8.25(dt,J=8.3,1.7Hz,1H),8.03-7.96(m ,1H),7.89-7.82(m,1H),7.54(ddd,J=8.2,6.0,2.1Hz,2H),7.20-7.12(m,1H),6.96(d,J=7.0Hz,2H),2.21(s,6H). 13 C NMR(100MHz,Benzene-d6)δ159.47,150.93,149.35,148.86,136.79,134.0 9,133.10,130.51,129.14,127.47,127.24,126.90,126.17,121.63,17.93.
[0042] Weigh 0.64g hafnium tetrachloride (2mmol), add 20mL anhydrous toluene, slowly add 3mL / 9mmol methylmagnesium bromide solution (3M) at -40℃ (using aluminum block as cooling medium), and stir for 2 hours. Add 0.52g 8-(2,6-Me2-C6H3-N=CH)-quinoline ligand L1 (2mmol), react for 2 hours at -40℃ in the dark, and continue to react for 4 hours at room temperature. After the reaction is completed, remove the solvent under reduced pressure (30℃ oil pump to extract the solvent, vacuum degree 1bar), add 20mL toluene, stir for 5 minutes, filter to obtain a yellow filtrate, and concentrate the filtrate (30℃ oil pump to extract the solvent, vacuum degree 1bar) to obtain 0.76g of product, with a yield of 78%. NMR data 1H NMR(400MHz,Chloroform-d)δ8.26(dd,J=6.6,1.7Hz,1H),7.81(dd,J=7.9,1.7Hz,1H),7.76(dd,J=7.8,6.6Hz,1H),7.49 -7.39(m,2H),7.17-7.06(m,2H),6.98(d,J=7.9Hz,2H),4.81(qd,J=7.9,0.6Hz,1H),2.07(s,6H),1.56(d,J=7.9Hz,3H). 13 C NMR(100MHz,Benzene-d6)δ151.35,138.01,136.36,135.34,134.98,134.22,130.55,127 .92,126.77,126.40,125.91,125.81,125.17,57.47,20.26,18.80,18.77,18.75,18.06.
[0043] Cat 1 structure is as follows:
[0044]
[0045] Synthesis Example 2, Preparation of Catalyst Cat 2
[0046] Weigh 0.79g of quinoline-8-carboxaldehyde (5mmol), add 20mL of anhydrous ethanol, slowly add 0.68g of 2,4,6-trimethylaniline (5mmol) at room temperature, add 5mg of p-toluenesulfonic acid to catalyze the reaction for 3 hours, remove the ethanol under reduced pressure, add anhydrous methanol to extract, and filter to obtain 1.13g of 8-(2,4,6-Me3-C6H3-N=CH)-quinoline ligand L2, with a yield of 82%. NMR data 1 HNMR(400MHz,Chloroform-d)δ8.90(dd,J=3.9,1.7Hz,1H),8.83(s,1H),8.25(dt,J=8.3,1.7Hz,1H),8.03-7. 96(m,1H),7.89-7.82(m,1H),7.54(ddd,J=8.2,6.0,2.1Hz,2H),6.89(d,J=0.8Hz,2H),2.27(d,J=1.0Hz,2H). 13C NMR(100MHz,Benzene-d6)δ159.23,149.36,149.35,148.86,136.79,133.85,1 33.10,131.29,130.51,129.14,128.71,127.47,127.24,121.63,20.77,18.16.
[0047] Weigh 0.64g hafnium tetrachloride (2mmol), add 20mL anhydrous toluene, slowly add 3mL / 9mmol methylmagnesium bromide solution (3M) at -40℃ (using aluminum block as cooling medium), and stir for 2 hours. Add 0.55g 8-(2,4,6-Me3-C6H3-N=CH)-quinoline ligand L2 (2mmol), react at -40℃ in the dark for 2 hours, return to room temperature and continue to react for 4 hours. After the reaction is completed, remove the solvent, add toluene to extract, filter, and concentrate the filtrate to obtain 0.83g of product with a yield of 80%. NMR data 1 H NMR(400MHz,Chloroform-d)δ8.26(dd,J=6.6,1.7Hz,1H),7.81(dd,J=7.9,1.7Hz,1H),7.76(dd,J=7.8,6.6Hz,1H),7.49-7.39(m,2 H),7.14(dd,J=8.3,1.8Hz,1H),6.78(s,2H),4.81(qd,J=7.9,0.6Hz,1H),2.26(d,J=0.9Hz,3H),1.95(s,4H),1.56(d,J=7.9Hz,3H). 13 C NMR(100MHz,Benzene-d6)δ148.09,138.01,136.27,135.34,135.05,134.98,134.22,130.55 ,128.58,126.77,126.40,125.81,125.17,57.47,20.68,20.26,18.80,18.77,18.75,18.27.
[0048] The structure of Cat 2 is as follows:
[0049]
[0050] Synthesis Example 3, Preparation of Catalyst Cat 3
[0051] Weigh 0.79g of quinoline-8-carboxaldehyde (5mmol), add 20mL of anhydrous ethanol, slowly add 0.82g of 2,4-dichloroaniline (5mmol) at room temperature, add 5mg of p-toluenesulfonic acid to catalyze the reaction for 3 hours, remove the ethanol under reduced pressure, add anhydrous methanol to extract, filter, and obtain 1.31g of 8-(2,6-Cl2-C6H3-N=CH)-quinoline ligand L3, with a yield of 86%. NMR data 1 H NMR(400MHz,Chloroform-d)δ9.03(s,1H),8.90(dd,J=3.9,1.7Hz,1H),8.25(dt,J=8.3,1.7Hz,1H),8.03-7.9 6(m,1H),7.92-7.85(m,1H),7.54(ddd,J=8.3,6.0,2.1Hz,2H),7.45-7.39(m,2H),7.30(dd,J=8.1,6.8Hz,1H). 13 C NMR (100MHz, Benzene-d6) δ159.66,149.35,148.68,147.01,136.79,133.59,130.51,130.17,129.74,129.14,127.47,127.32,126.28,121.63.
[0052] Weigh 0.64g hafnium tetrachloride (2mmol), add 20mL anhydrous toluene, slowly add 3mL / 9mmol methylmagnesium bromide solution (3M) at -40℃ (using aluminum block as cooling medium), and stir for 2 hours. Add 0.61g 8-(2,6-Cl2-C6H3-N=CH)-quinoline ligand L3 (2mmol), react at -40℃ in the dark for 2 hours, return to room temperature and continue to react for 4 hours. After the reaction is completed, remove the solvent, add toluene to extract, filter, and concentrate the filtrate to obtain 0.84g of product with a yield of 78%. NMR data 1 H NMR(400MHz,Chloroform-d)δ8.26(dd,J=6.6,1.7Hz,1H),7.84-7.72(m,2H),7.49-7.39(m,2H),7.31 (d,J=1.3Hz,1H),7.29(s,1H),7.24-7.10(m,2H),4.78(qd,J=7.8,0.6Hz,1H),1.56(d,J=7.9Hz,3H). 13C NMR(100MHz,Benzene-d6)δ148.17,138.01,135.36,134.98,134.20,132.22,130.55, 128.34,127.11,126.77,126.40,125.81,125.17,57.44,20.37,18.81,18.79,18.77.
[0053] The structure of Cat 3 is as follows:
[0054]
[0055] Synthesis Example 4, Preparation of Catalyst Cat 4
[0056] Weigh 0.79g of quinoline-8-carboxaldehyde (5mmol), add 20mL of anhydrous ethanol, slowly add 0.89g of 2,6-diisopropylaniline (5mmol) at room temperature, add 5mg of p-toluenesulfonic acid to catalyze the reaction for 3 hours, remove the ethanol under reduced pressure, add anhydrous methanol to extract, filter, and obtain 1.31g of 8-(2,6-i-Pr2-C6H3-N=CH)-quinoline ligand L4, with a yield of 97%. NMR data 1 HNMR(400MHz,Chloroform-d)δ8.90(dd,J=3.9,1.7Hz,1H),8.84(d,J=0.6Hz,1H),8.25(dt,J=8.3,1.7Hz,1H),8.03-7.96(m,1H),7.92-7.86( m,1H),7.54(ddd,J=8.3,6.0,2.1Hz,2H),7.26(dd,J=8.3,6.4Hz,1H),7.19(dd,J=7.3,0.8Hz,2H),3.14-3.00(m,2H),1.27(d,J=6.2Hz,12H). 13 C NMR(100MHz,Benzene-d6)δ159.25,149.35,148.86,146.04,137.78,136.79,1 33.31,130.51,129.14,127.92,127.47,127.25,124.65,121.63,29.43,22.25.
[0057] Weigh 0.64g hafnium tetrachloride (2mmol), add 20mL anhydrous toluene, slowly add 3mL / 9mmol methylmagnesium bromide solution (3M) at -40℃ (using aluminum block as cooling medium), and stir for 2 hours. Add 8-(2,6-i-Pr2-C6H3-N=CH)-quinoline ligand L4 (0.63g, 2mmol), react at -40℃ in the dark for 2 hours, return to room temperature and continue to react for 4 hours. After the reaction is completed, remove the solvent, extract with toluene, filter, and concentrate the filtrate to obtain 1.03g of product with a yield of 92%. NMR data 1 HNMR(400MHz,Chloroform-d)δ8.26(dd,J=6.6,1.7Hz,1H),7.81(dd,J=7.9,1.7Hz,1H),7.76(dd,J=7.8,6.6Hz,1H),7.49-7.39(m,2H),7.32(t,J=8.3Hz, 1H),7.14(dd,J=8.2,1.9Hz,1H),7.10-7.03(m,2H),4.83(qd,J=7.9,0.6Hz, 1H),3.26-3.11(m,2H),1.56(d,J=7.9Hz,3H),1.22(dd,J=19.9,6.9Hz,12H). 13 C NMR(100MHz,Benzene-d6)δ149.03,145.21,138.01,135.34,134.98,134.22,130.55,127.21 ,126.77,126.40,125.81,125.17,124.51,57.63,29.14,24.28,20.26,18.80,18.77,18.75.
[0058] The structure of Cat 4 is as follows:
[0059]
[0060] Synthesis Example 5, Preparation of Catalyst Cat 5
[0061] Weigh 0.38g titanium tetrachloride (2mmol), add 20mL anhydrous toluene, slowly add 3mL / 9mmol methylmagnesium bromide solution (3M) at -40℃ (using aluminum block as cooling medium), and stir for 2 hours. Add 0.63g 8-(2,6-i-Pr2-C6H3-N=CH)-quinoline ligand L4 (2mmol), react at -40℃ in the dark for 2 hours, return to room temperature and continue to react for 4 hours. After the reaction is completed, remove the solvent, add toluene to extract and filter to obtain 0.70g of product with a yield of 82%. NMR data 1H NMR(400MHz,Chloroform-d)δ8.36(dd,J=6.9,1.4Hz,1H),7.93(ddt,J=7.6,6.0,1.6 Hz, 2H), 7.71 (dd, J=8.1, 6.8Hz, 1H), 7.25 (dt, J=8.9, 0.9Hz, 1H), 7.18 (dd, J=9.3, 7. 1Hz, 1H), 7.10 (dd, J=8.1, 1.0Hz, 2H), 4.55 (qd, J=7.8, 0.6Hz, 1H), 3.06 (heptd, J=7. 0,0.6Hz,2H),1.50(s,1H),1.25(d,J=6.8Hz,5H),1.20(d,J=6.8Hz,6H),1.03(s,9H). 13 C NMR(100MHz,Benzene-d6)δ148.48,145.21,137.93,135.47,134.61,134.25,130.85, 127.21,126.77,126.38,125.79,125.22,124.52,57.82,29.03,24.28,22.15,20.33.
[0062] The structural formula of Cat 5 is as follows:
[0063]
[0064] Synthesis Example 6, Preparation of Catalyst Cat 6
[0065] Weigh 0.47g zirconium tetrachloride (2mmol), add 20mL anhydrous toluene, slowly add 3mL / 9mmol methylmagnesium bromide solution (3M) at -40℃ (using aluminum block as cooling medium), and stir for 2 hours. Add 0.63g 8-(2,6-i-Pr2-C6H3-N=CH)-quinoline ligand L4 (2mmol), react for 3 hours at -40℃ in the dark, and continue to react for 6 hours at room temperature. After the reaction is completed, remove the solvent, add toluene to extract, filter, and concentrate the filtrate to obtain 0.72g of product with a yield of 76%. NMR data 1 H NMR(400MHz,Chloroform-d)δ7.94(ddt,J=10.4,8.3,1.5Hz,1H),7.27-7.14(m,1H),7.12 -7.05(m,1H),3.11-2.96(m,1H),1.52(s,0H),1.23(dd,J=19.9,6.8Hz,4H),1.04(s,3H). 13C NMR(100MHz,Benzene-d6)δ148.69,145.09,138.03,135.44,135.41,133.86,130.86, 127.21,126.77,126.39,125.75,125.24,124.40,57.66,29.04,24.28,21.62,20.29.
[0066] The structural formula of Cat 6 is as follows:
[0067]
[0068] Example A1
[0069] Cat 1|MAO prepared in Synthesis Example 1 is used to catalyze ethylene polymerization, comprising the following steps:
[0070] At room temperature, add 2000mL of cyclohexane to a 5L stainless steel reactor that has been evacuated in advance and replaced with nitrogen, turn on mechanical stirring, keep 600 rpm, start heating, when the temperature reaches 120°C, inject ethylene into the reactor, set the reactor ethylene pressure to 3.0MPa, after reaching the set pressure, pre-dissolve for 30min, then add 30mL cyclohexane solution dissolved with 20μmol of Cat 1 and 8mL co-catalyst MAO (Al / Hf=500) to the reactor by a high-pressure pump, and the polymerization reaction begins. During the reaction, keep the reaction temperature, ethylene pressure and stirring rate unchanged. After 30min, the reaction is complete, the gas in the reactor is emptied through the vent valve, the reaction solution is neutralized with a 5%wt hydrochloric acid acidified ethanol solution, a polymer is obtained and washed with ethanol several times, vacuum dried to constant weight, and 152g of polymer is obtained by weighing, which is polyethylene.
[0071] The polymerization activity of the obtained polyethylene was calculated and GPC was measured. The results were as follows: polymerization activity 1.52×10 7 g·mol -1 (Hf)h -1 , polymer M w =3.23×10 5 g·mol -1 , M w / M n =2.4, T m (Polymer melting point) = 126.3°C.
[0072] Example A2
[0073] Cat 1|MAO prepared in Synthesis Example 1 was used to catalyze ethylene polymerization, which was different from Example A1 only in that the polymerization temperature was 100° C., and 148 g of polymer (polyethylene) was obtained.
[0074] The polymerization activity was determined to be 1.48×10 7 g·mol -1 (Hf)h -1 , polymer M w =3.42×10 5 g·mol -1 , M w / M n =2.1, T m (Polymer melting point) = 126.5°C.
[0075] Example A3
[0076] Cat 1|MAO prepared in Synthesis Example 1 was used to catalyze ethylene polymerization, which was different from Example A1 only in that the polymerization temperature was 130° C., and 138 g of polymer (polyethylene) was obtained.
[0077] The polymerization activity was determined to be 1.38×10 7 g·mol -1 (Hf)h -1 , polymer M w =2.94×10 5 g·mol -1 , M w / M n =3.2, T m (Polymer melting point) = 126°C.
[0078] Example A4
[0079] Cat 1|MAO prepared in Synthesis Example 1 was used to catalyze ethylene polymerization, which was different from Example A1 only in that the polymerization temperature was 140° C. and 130 g of polymer was obtained.
[0080] The polymerization activity was determined to be 1.30×10 7 g·mol -1 (Hf)h -1 , polymer M w =2.44×10 5 g·mol -1 , M w / M n =6.4, T m (Polymer melting point) = 123°C.
[0081] Example A5
[0082] Cat 1|MAO prepared in Synthesis Example 1 was used to catalyze ethylene polymerization. The only difference from Example A1 was that the polymerization reaction temperature remained unchanged, the amount of co-catalyst added was changed, and 16 mL of co-catalyst MAO (Al / Hf=1000) was added to obtain 178 g of polymer.
[0083] The polymerization activity was determined to be 1.68×10 7 g·mol -1 (Hf)h -1 , polymer M w =4.06×10 5 g·mol -1 , M w / M n =3.0, T m (Polymer melting point) = 130°C.
[0084] From Examples A1-A4, it can be seen that Cat 1|MAO catalyzes ethylene polymerization, and the catalytic activity is relatively high within the temperature window of 100°C to 140°C (distributed in the range of 1.30×10 7 g·mol -1 (Hf)h -1 ~1.52×10 7 g·mol -1 (Hf)h -1 From Example A1 and Example A5, it can be seen that in Cat 1|MAO catalyst, a ratio of the two ranging from 500:1 to 1000:1 can achieve higher catalytic activity and narrower molecular weight distribution.
[0085] Example A6
[0086] Cat 2|MAO prepared in Synthesis Example 2 was used to catalyze ethylene polymerization, which was different from Example A1 only in that the polymerization temperature was 120° C., 20 μmol Cat 2 was added as the main catalyst, and 142 g of polymer was obtained.
[0087] The polymerization activity was measured to be 1.42×10 7 g·mol -1 (Hf)h -1 , polymer M w =3.56×10 5 g·mol -1 , M w / M n =3.1, T m (Polymer melting point) = 126°C.
[0088] Example A7
[0089] Cat 3|MAO prepared in Synthesis Example 3 was used to catalyze ethylene polymerization, which was different from Example A1 only in that the polymerization temperature was 120° C., 20 μmol of complex Cat 3 was added as the main catalyst, and 138 g of polymer was obtained.
[0090] The polymerization activity was determined to be 1.38×107 g·mol -1 (Hf)h -1 , polymer M w =3.16×10 5 g·mol -1 , M w / M n =3.1, T m (Polymer melting point) = 124°C.
[0091] Example A8
[0092] Cat 4|MAO prepared in Synthesis Example 4 was used to catalyze ethylene polymerization, which was different from Example A1 only in that the polymerization temperature was 120° C., 20 μmol Cat 4 was added as the main catalyst, and 162 g of polymer was obtained.
[0093] The polymerization activity was measured to be 1.62×10 7 g·mol -1 (Hf)h -1 , polymer M w =2.42×10 5 g·mol -1 , M w / M n =2.2, T m (Polymer melting point) = 128°C.
[0094] Embodiment A9
[0095] Cat 5|MAO prepared in Synthesis Example 5 was used to catalyze ethylene polymerization, which was different from Example A1 only in that the polymerization temperature was 120° C., 20 μmol Cat 5 was added as the main catalyst, and 116 g of polymer was obtained.
[0096] The polymerization activity was measured to be 1.16×10 7 g·mol -1 (Ti)h -1 , polymer M w =2.64×10 5 g·mol -1 , M w / M n =3.8, T m (Polymer melting point) = 133°C.
[0097] Embodiment A10
[0098] Cat 6|MAO prepared in Synthesis Example 6 was used to catalyze ethylene polymerization, which was different from Example A1 only in that the polymerization temperature was 120° C., 20 μmol Cat 6 was added as the main catalyst, and 122 g of polymer was obtained.
[0099] The polymerization activity was determined to be 1.22×10 7 g·mol -1 (Zr)h -1 , polymer M w =2.25×10 5 g·mol -1 , M w / M n =3.8, T m (Polymer melting point) = 125°C.
[0100] It can be seen from Examples A1 to A10 that the bidentate metal catalysts containing the quinoline skeleton [NN] provided in the present application all have high polymerization activity for catalyzing ethylene polymerization, among which Cat 4 has the best catalytic activity.
[0101] Example B1
[0102] Cat 4|MAO prepared in Synthesis Example 4 was used to catalyze ethylene / 1-octene polymerization, comprising the following steps:
[0103] Under room temperature, add 2000mL cyclohexane and 210g 1-octene in the 5L stainless steel reactor that has been evacuated in advance and replaced with nitrogen, open mechanical stirring, keep 600 rev / min, start heating, when temperature reaches 120 ℃, inject ethylene in reactor, setting reactor ethylene pressure is 3.0MPa, after arriving setting pressure, pre-dissolve 30min, then by high-pressure pump, 30mL cyclohexane solution that has dissolved Cat 4 (20 μ mol) and cocatalyst MAO (Al / Hf=500) (8mL) is added reactor, polyreaction begins.In reaction process, keep reaction temperature, ethylene pressure and stir speed constant.After 30min, reaction is complete, and gas in the still is emptied by vent valve, neutralize reaction solution with ethanol solution acidified with 5%wt hydrochloric acid, obtain polymkeric substance and wash with ethanol for several times, vacuum drying is to constant weight, weigh and obtain 136g polymkeric substance, be ethylene / 1-octene copolymer.
[0104] The polymerization activity of the obtained copolymer was calculated and GPC was measured. The results were as follows: polymerization activity 1.36×10 7 g·mol -1 (Hf)h -1 , polymer M w =2.84×10 5 g·mol -1 , M w / M n =2.3, 1-octene insertion rate 22.8 mol%.
[0105] Example B2
[0106] Cat 4|MAO prepared in Synthesis Example 4 was used to catalyze ethylene / 1-octene polymerization, which was different from Example B1 only in that the polymerization temperature was 100° C., 20 μmol Cat 4 was added as the main catalyst, and 103 g of polymer was obtained.
[0107] The polymerization activity was measured to be 1.03×10 6 g·mol -1 (Hf)h -1 , polymer M w =3.2×10 5 g·mol -1 , M w / M n =2.0, 1-octene insertion rate 25.6 mol%.
[0108] Example B3
[0109] Cat 4|MAO prepared in Synthesis Example 4 was used to catalyze ethylene / 1-octene polymerization, which was different from Example B1 only in that the polymerization temperature was 130° C., 20 μmol Cat 4 was added as the main catalyst, and 100 g of polymer was obtained.
[0110] The polymerization activity was determined to be 1.0×10 7 g·mol -1 (Hf)h -1 , polymer M w =2.53×10 5 g·mol -1 , M w / M n =2.6, 1-octene insertion rate 19.5 mol%.
[0111] Example B4
[0112] Cat 4|MAO prepared in Synthesis Example 4 was used to catalyze ethylene / 1-octene polymerization, which was different from Example B1 only in that the polymerization temperature was 140° C., 20 μmol Cat 4 was added as the main catalyst, and 89 g of polymer was obtained.
[0113] The polymerization activity was determined to be 0.89×10 7 g·mol -1 (Hf)h -1 , polymer M w =2.32×10 5 g·mol -1 , M w / M n =3.0, T m (Polymer melting point) = 92°C, 1-octene insertion rate 10.9 mol%.
[0114] From Examples B1-B4, it can be seen that Cat 4|MAO has a high catalytic activity in the temperature window of 100°C to 140°C (distributed in the range of 0.89×10 7 g·mol -1 (Hf)h -1 ~1.36×10 7 g·mol -1 (Hf)h -1 Between), narrow molecular weight distribution (M w / M n Distributed between 2.0 and 3.0).
[0115] Example B5
[0116] Cat 1|MAO prepared in Synthesis Example 1 was used to catalyze ethylene / 1-octene polymerization, which was different from Example B1 only in that the polymerization temperature was 120° C., 20 μmol Cat 1 was added as the main catalyst, and 78 g of polymer was obtained.
[0117] The polymerization activity was measured to be 0.78×10 7 g·mol -1 (Hf)h -1 , polymer M w =2.42×10 5 g·mol -1 , M w / M n =2.6, 1-octene insertion rate 14.6 mol%.
[0118] Example B6
[0119] Cat 2|MAO prepared in Synthesis Example 2 was used to catalyze ethylene / 1-octene polymerization, which was different from Example B1 only in that the polymerization temperature was 120° C., 20 μmol Cat 2 was added as the main catalyst, and 83 g of polymer was obtained.
[0120] The polymerization activity was measured to be 0.83×10 7 g·mol -1 (Hf)h -1 , polymer M w =2.32×10 5 g·mol -1 , M w / M n =3.6, 1-octene insertion rate 16.8 mol%.
[0121] Example B7
[0122] Cat 3|MAO prepared in Synthesis Example 3 was used to catalyze ethylene / 1-octene polymerization, which was different from Example B1 only in that the polymerization temperature was 120° C., 20 μmol Cat 3 was added as the main catalyst, and 92 g of polymer was obtained.
[0123] The polymerization activity was measured to be 0.92×10 7 g·mol -1 (Hf)h -1 , polymer M w =2.66×10 5 g·mol -1 , M w / M n =3.2, 1-octene insertion rate 17.2 mol%.
[0124] Example B8
[0125] Cat 5|MAO prepared in Synthesis Example 5 was used to catalyze ethylene / 1-octene polymerization, which was different from Example B1 only in that the polymerization temperature was 120° C., 20 μmol Cat 5 was added as the main catalyst, and 68 g of polymer was obtained.
[0126] The polymerization activity was measured to be 0.68×10 7 g·mol -1 (Ti)h -1 , polymer M w =2.45×10 5 g·mol -1 , M w / M n =3.2, 1-octene insertion rate 18.4 mol%.
[0127] Example B9
[0128] Cat 6|MAO prepared in Synthesis Example 6 was used to catalyze ethylene / 1-octene polymerization, which was different from Example B1 only in that the polymerization temperature was 120° C., 20 μmol Cat 6 was added as the main catalyst, and 76 g of polymer was obtained.
[0129] The polymerization activity was measured to be 0.76×10 7 g·mol -1 (Zr)h -1 , polymer M w =2.51×10 5 g·mol -1 , M w / M n =2.6, 1-octene insertion rate 20.6 mol%.
[0130] From Examples B1 to B9, it can be seen that the bidentate metal catalyst containing the quinoline skeleton [NN] provided in the present application has a high polymerization activity in the copolymerization reaction of ethylene and α-olefin, and the molecular weight distribution of the copolymer is narrow, and the insertion rate of α-olefin is high. At 140°C, it still has a high polymerization activity and α-olefin insertion rate, which shows that the quinoline skeleton [NN] bidentate metal catalyst provided in the present application has good thermal stability.
[0131] Example B10
[0132] Cat 4|MAO prepared in Synthesis Example 4 was used to catalyze ethylene / 1-octene polymerization. The only difference from Example B1 was that the polymerization reaction temperature remained unchanged, the amount of co-catalyst added was changed, and 16 mL of co-catalyst MAO (Al / Hf=1000) was added to obtain 145 g of polymer.
[0133] The polymerization activity was determined to be 1.45×10 7 g·mol -1 (Zr)h -1 , polymer M w =2.85×10 5 g·mol -1 , M w / M n =2.5, 1-octene insertion rate 19.8 mol%.
[0134] Example B11
[0135] Cat 4|MAO prepared in Synthesis Example 4 was used to catalyze ethylene / 1-octene polymerization. The only difference from Example B1 was that the polymerization reaction temperature remained unchanged, the amount of co-catalyst added was changed, and 1.6 mL of co-catalyst MAO (Al / Hf=100) was added to obtain 76 g of polymer.
[0136] The polymerization activity was measured to be 0.76×10 6 g·mol -1 (Hf)h -1 , polymer M w =2.02×10 5 g·mol -1 , M w / M n =2.3, 1-octene insertion rate 10.2 mol%.
[0137] Example B12
[0138] Cat 4|MAO prepared in Synthesis Example 4 was used to catalyze ethylene / 1-octene polymerization. The only difference from Example B1 was that the polymerization reaction temperature remained unchanged, the amount of co-catalyst added was changed, and 20 mL of co-catalyst MAO (Al / Hf=2000) was added to obtain 162 g of polymer.
[0139] The polymerization activity was measured to be 1.62×10 7 g·mol -1 (Hf)h -1 , polymer M w =2.8×10 5 g·mol -1 , M w / M n =2.1, 1-octene insertion rate 21.6 mol%.
[0140] From Examples B1, B10 to B12, it can be seen that when the complex provided in the present application is used as the main catalyst, the ratio of the complex provided in the present application to the co-catalyst MAO catalyst is from 100 to 2000, which can catalyze the copolymerization of ethylene and α-olefins and obtain a higher polymerization activity. It should be noted that the ratio of the complex provided in the present application as the main catalyst to the co-catalyst MAO catalyst can also be selected other than 100 to 2000.
[0141] Comparative Example 1
[0142] Using CGC catalyst [Me2Si(C5Me4)(N t Bu)]TiMe2 catalyzes ethylene / 1-octene polymerization, comprising the following steps:
[0143] At room temperature, 2000 mL of cyclohexane and 210 g of 1-octene were added to a 5 L stainless steel reactor that had been evacuated and replaced with nitrogen in advance. The mechanical stirring was turned on and maintained at 600 rpm. The temperature was started to rise. When the temperature reached 120° C., ethylene was injected into the reactor. The ethylene pressure of the reactor was set to 3.0 MPa. After reaching the set pressure, the reactor was pre-dissolved for 30 min, and then the dissolved CGC catalyst [Me2Si(C5Me4)(N t Bu)]TiMe2 (20 μmol) and 30 mL cyclohexane solution of co-catalyst MAO (Al / Ti=500) (8 mL) were added to the reactor, and the polymerization reaction began. During the reaction, the reaction temperature, ethylene pressure and stirring rate were kept unchanged. After 30 minutes, the reaction was completed, and the gas in the reactor was emptied through the vent valve. The reaction solution was neutralized with an ethanol solution acidified with 5%wt hydrochloric acid to obtain a polymer, which was washed several times with ethanol, and vacuum dried to constant weight. 90 g of the polymer was weighed, which was an ethylene / 1-octene copolymer.
[0144] The polymerization activity of the obtained copolymer was calculated and GPC was measured. The results were as follows: polymerization activity 0.9×10 7 g·mol -1 (Ti)h -1 , polymer M w =2.32×10 5 g·mol -1 , M w / M n =3.5, 1-octene insertion rate 10.6 mol%.
[0145] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A quinoline skeleton [NN] bidentate coordination metal catalyst, characterized in that: The structural formula is shown in formula (I): In formula (I), M is selected from any one of titanium, zirconium or hafnium; in formula (I), R1, R2, and R3 are selected from any one of fluorine, chlorine, bromine, iodine, and alkyl.
2. A quinoline skeleton [NN] bidentate coordination metal catalyst according to claim 1, characterized in that: The quinoline ligand structural formula of the quinoline skeleton [NN] bidentate coordination metal catalyst is selected from any one of the formula (II):
3. The method for preparing a quinoline skeleton [NN] bidentate coordination metal catalyst according to claim 1, characterized in that: The following steps are involved: Under nitrogen atmosphere, 0.6-1.5 g of quinoline-8-carboxaldehyde is dissolved in 10-30 mL of ethanol solvent, the molar concentration of the ethanol solvent is 0.2-1.0 mol / L, 1.0-1.5 molar equivalents of aniline and 5-10 mg of p-toluenesulfonic acid are added, and the mixture is reacted at room temperature for 3 hours; after removing the ethanol under reduced pressure, anhydrous methanol is added for extraction and filtration to obtain a quinoline-imine ligand; 1.0-1.2 molar equivalents of metal chloride MCl4 are dissolved in 10-50 mL of anhydrous solvent, 4.0-6.0 molar equivalents of methylmagnesium bromide are added, and the mixture is stirred at -20--50° C. for 2 hours under nitrogen protection, and then 1 molar equivalent of quinoline-imine ligand is added, and the mixture is stirred at -20--50° C. for 2 hours and at room temperature for 4 hours; the solvent is removed under reduced pressure, extracted with a good solvent, and the filtrate is concentrated to obtain a quinoline skeleton [NN] bidentate coordination metal catalyst.
4. The method for preparing a quinoline skeleton [NN] bidentate coordination metal catalyst according to claim 3, characterized in that: The anhydrous solvent is selected from any one of benzene, toluene and xylene; the good solvent is selected from any one of n-hexane, cyclohexane, n-pentane, n-heptane and toluene.
5. The method for preparing a quinoline skeleton [NN] bidentate coordination metal catalyst according to claim 3, characterized in that: The metal chloride MCl4 is selected from one of TiCl4, ZrCl4 and HfCl4.
6. A quinoline skeleton [NN] bidentate coordination metal catalyst according to claim 1, characterized in that: Application in the preparation of polyolefins.
7. Use of a quinoline skeleton [NN] bidentate coordination metal catalyst in the preparation of polyolefins according to claim 6, characterized in that: The olefin monomer in the polyolefin is one or more of ethylene, propylene, 1-butene, 1-hexene, 1-octene, styrene and norbornene.
8. Use of a quinoline skeleton [NN] bidentate coordination metal catalyst in the preparation of polyolefins according to claim 6, characterized in that: The quinoline skeleton [NN] bidentate coordination metal catalyst is used in combination with a co-catalyst to catalyze olefin polymerization, and the co-catalyst is one or more of trispentafluorophenyl boron, trityltetrakis(pentafluorophenyl)borate, alkyl aluminum, and aluminoxane.
9. Use of a quinoline skeleton [NN] bidentate coordination metal catalyst in the preparation of polyolefins according to claim 8, characterized in that: The alkylaluminum is trimethylaluminum, triethylaluminum, triisobutylaluminum or tri-n-hexylaluminum; the aluminoxane is methylaluminoxane, ethylaluminoxane or isobutylaluminoxane.
10. Use of a quinoline skeleton [NN] bidentate coordination metal catalyst in the preparation of polyolefins according to claim 8, characterized in that: In the olefin polymerization reaction, the polymerization temperature is 0-200° C., the polymerization pressure is 0.1-5 MPa, and the polymerization solvent is one or more of toluene, xylene, n-hexane, and cyclohexane.
Citation Information
Patent Citations
Preparation of trihydroquinolinamine metal compounds and application of trihydroquinolinamine metal compounds in high temperature solution polymerization of olefin
CN110698513A
Olefin polymerization catalyst, olefin polymerization catalyst composition and method for preparing polyolefin
CN111484574A
Preparation method and application of NN-bidentate coordination metal catalyst based on quinoline skeleton
CN118047806A
Novel transition metal compound
KR1020170069044A
Method of preparing novel transition metal compound
KR1020170069045A
Cited By
Preparation method of post-metallocene catalyst
CN120590564A
A method for the preparation of a post-metallocene catalyst
CN120590564B